Entre la infamia y el deleite. Las cobradoras de tranvías en Santiago de Chile y Valparaíso, 1880-1920 - Elisabet Prudant Soto (Nuevo mundo - Mundos Nuevos, 2009)
This work sets out to recognize in the urban scenes of Santiago and Valparaiso the diverse constructed sex-generic images around the figure of the cobradoras of streetcars, between years 1880 and 1920. From a specific conjuncture, the War of the Pacific and its implications like process extractor of masculine manpower towards the north of the country, are investigated in the symbolic repercussions that the “visibilization” of this group of wage women generated in the public space. The case of the cobradoras of streetcars allows to determine the proportions how the feminine participation in a masculine labor field, generated ideologized opinions, reflection of the imaginary that were cultivated on the feminine work during this period.